THE INFLUENCE OF ACADEMIC SUPERVISION AND SCHOOL CLIMATE ON TEACHER PERFORMANCE AT PUBLIC ELEMENTARY SCHOOLS IN WEST PRINGSEWU - Nurhayati, Hamidah; Aswad, Fatqul Hajar (Institut Bakti Nusantara, 2025)
Teacher performance plays a critical role in determining the quality of educational outcomes at the primary school level. This study aims to examine the influence of principals’ academic supervision and school climate on teachers’ performance at public elementary schools in Pringsewu Barat, Indonesia. A quantitative research design was employed using a survey method. Data were collected through structured questionnaires distributed to teachers, and the obtained data were analyzed using descriptive and inferential statistical techniques. Multiple regression analysis was applied to determine both the partial and simultaneous effects of academic supervision and school climate on teachers’ performance. The findings indicate that principals’ academic supervision has a positive and statistically significant effect on teachers’ performance. Effective supervision, characterized by professional guidance, constructive feedback, and continuous support, contributes to improving teachers’ instructional practices and professional competence. In addition, school climate was found to have a significant positive influence on teachers’ performance. A supportive, value-based, and conducive school environment fosters teachers’ motivation, job satisfaction, and commitment to instructional improvement. Furthermore, the simultaneous analysis reveals that principals’ academic supervision and school climate collectively account for 64.9% of the variance in teachers’ performance, while the remaining 35.1% is influenced by other factors not examined in this study. These results highlight the strategic importance of integrating effective academic supervision with the development of a positive school climate to enhance teacher performance. This study contributes to the literature on educational management by providing empirical evidence from the primary education context. Practically, the findings suggest that school leaders and education authorities should strengthen supervision practices and cultivate a supportive school climate as key strategies for improving teaching quality and teacher professionalism.